Time for prediction? The effect of presentation rate on predictive sentence comprehension during word-by-word reading. (July 2015) - Wlotko, Edward W.; Federmeier, Kara D.
Abstract: Predictive processing is a core component of normal language comprehension, but the brain may not engage in prediction to the same extent in all circumstances. This study investigates the effects of timing on anticipatory comprehension mechanisms. Event-related brain potentials (ERPs) were recorded while participants read two-sentence mini-scenarios previously shown to elicit prediction-related effects for implausible items that are categorically related to expected items ('They wanted to make the hotel look more like a tropical resort. So along the driveway they planted rows of PALMS/PINES/TULIPS.'). The first sentence of every pair was presented in its entirety and was self-paced. The second sentence was presented word-by-word with a fixed stimulus onset asynchrony (SOA) of either 500 msec or 250 msec that was manipulated in a within-subjects blocked design. Amplitudes of the N400 ERP component are taken as a neural index of demands on semantic processing. At 500 msec SOA, implausible words related to predictable words elicited reduced N400 amplitudes compared to unrelated words (PINES vs  TULIPS), replicating past studies. At 250 msec SOA this prediction-related semantic facilitation was diminished. Thus, timing is a factor in determining the extent to which anticipatory mechanisms are engaged. However, we found evidence that prediction can sometimes be engaged even under speeded presentation rates. Participants who first read sentences in the 250 msec SOA block showed no effect of semantic similarity for this SOA, although these same participants showed the effect in the second block with 500 msec SOA. However, participants who first read sentences in the 500 msec SOA block continued to show the N400 semantic similarity effect in the 250 msec SOA block. These findings add to results showing that the brain flexibly allocates resources to most effectively achieve comprehension goals given the current processing environment.